Adiposity - Omics and Molecular Understanding 2017
DOI: 10.5772/66128
|View full text |Cite
|
Sign up to set email alerts
|

New Thoughts on Pediatric Genetic Obesity: Pathogenesis, Clinical Characteristics and Treatment Approach

Abstract: Historically, some genetic syndromes and monogenic forms of obesity have been identified by clinical features and by sequencing candidate genes in patients with severe obesity. The phenotypic expression of genetic factors involved in obesity is variable, thereby allowing to distinguish several clinical pictures of obesity. Monogenic obesity is described as rare and severe early-onset obesity with abnormal feeding behavior and endocrine disorders. Many of the findings emerged from studying families who displaye… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
1
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 204 publications
(298 reference statements)
0
1
0
Order By: Relevance
“…In this study, we showed that APOC3 rs2854116 C-allele carrier patients have a six-fold higher risk of developing MAFLD in a dominant model. Our findings are also consistent with previous reports that the APOC3 rs2854116 genetic variant leads to increased plasma concentrations of apolipoprotein C3, resulting in hepatic insulin resistance and MAFLD in multiethnic populations[ 23 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In this study, we showed that APOC3 rs2854116 C-allele carrier patients have a six-fold higher risk of developing MAFLD in a dominant model. Our findings are also consistent with previous reports that the APOC3 rs2854116 genetic variant leads to increased plasma concentrations of apolipoprotein C3, resulting in hepatic insulin resistance and MAFLD in multiethnic populations[ 23 , 45 , 46 ].…”
Section: Discussionsupporting
confidence: 93%
“…The polymorphism in the promotor region of the APOC3 rs2854116 (-455T>C) gene has been extensively studied and has been found to be related with insulin resistance at the transcriptional level. Consequently, the overexpression of APOC3 , which functions to inhibit lipoprotein lipase and the cellular uptake of triglyceride-rich lipoprotein particles, may result in hypertriglyceridemia, as has been confirmed by in vivo and clinical studies[ 23 , 24 , 42 - 44 ]. In this study, we showed that APOC3 rs2854116 C-allele carrier patients have a six-fold higher risk of developing MAFLD in a dominant model.…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…Syndromic obesity includes Bardet-Biedl, Prader-Willi, Alstrom, and Smith-Magenis syndromes, characterized by obesity as the predominant phenotype and associated with disorders such as mental retardation, congenital defects in organs, dysmorphism of the limbs, or endocrine and facial dysfunction. Although numerous studies have revealed the genes or chromosomal regions involved in the etiology of many of these syndromes, their relationship with the development of obesity is still unknown [10,20,55]. Bardet-Biedel syndrome (BBS) is a rare autosomal recessive ciliopathy, characterized by retinal dystrophy, obesity, post-axial polydactyly, renal dysfunction, mental retardation, and hypogonadism.…”
Section: Syndromic Obesitymentioning
confidence: 99%